2019
DOI: 10.1007/s12471-019-1271-0
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in characteristics and outcome in acute coronary syndrome patients in the Netherlands

Abstract: Background Sex differences in acute coronary syndrome (ACS) have been reported, but little is known about the situation in the Netherlands. Methods This registry is a merge of available data on ACS patients in the electronic data capture systems of 11 centres with 24/7 interventional cardiology services. We included patients >18 years undergoing a cardiac catheterisation between 2010–2012. We evaluated sex differences in clinical and procedural characteristics and 1‑yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 31 publications
5
25
2
Order By: Relevance
“…This concurs with a previous study with a similar age distribution. 34 Our study showed that 53.2% of the patients had diastolic dysfunction, which is also like other studies. 35 , 36 Valvular disease was more prevalent in the non-ischemic group, as reported previously.…”
Section: Discussionsupporting
confidence: 91%
“…This concurs with a previous study with a similar age distribution. 34 Our study showed that 53.2% of the patients had diastolic dysfunction, which is also like other studies. 35 , 36 Valvular disease was more prevalent in the non-ischemic group, as reported previously.…”
Section: Discussionsupporting
confidence: 91%
“…Khan et al have found a higher proportion of family history of premature coronary artery diseases among females than males in a study done on young patients [21]. However, a study done in Netherland has revealed a low prevalence of family history of coronary artery disease in females (40.2%) than the male (42.1%) with ACS [22]. There was no signi cant difference in family histories of IHD, diabetes mellitus, stroke or dyslipidaemia in our population.…”
Section: Discussioncontrasting
confidence: 49%
“…Furthermore, an increased inflammatory response was associated with no-reflow and higher mortality post-STEMI. Another study showed that women younger than 71 years have a higher one-year mortality compared to the older women, whereas older women had a lower mortality compared to older men 21 . Our study is of additive value, since it provides a comprehensive overview of the leukocyte profiles directly after MI and their potential associations with outcome.…”
Section: Discussionmentioning
confidence: 98%